Publish ethically or perish - Arjumand S Warsy; Irfan Ahmad Warsy (Wolters Kluwer Medknow Publications, 2019)
The phrase "publish or perish" has been used in an academic context since the early 1970s to emphasize the importance of publishing the findings of research. It has also been widely used to describe the pressure in academic institutions to rapidly and continually publish academic work. The pressure to publish, the lack of knowledge about publication ethics, and other factors have led occasional authors to indulge in practices that are outside of the realm of the ethical principles. This article highlights the ethics of writing and publishing, outlines the various unethical practices (misconduct) that must be avoided, and highlights the severe consequences that may be inflicted on an author, whether a junior or a senior one, following detection of misconducts in publishing. The title of this article is a modified form of the maxim "publish or perish" because it is an important responsibility that every author publishes ethically.